1957
DOI: 10.1055/s-0038-1656211
|View full text |Cite
|
Sign up to set email alerts
|

The blood coagulation mechanisms in thrombocytopenic blood

Abstract: SummaryThrombocytopenic serum supports a short prothrombin consumption time, however, the same serum contains as little prothrombin as normal serum. The prothrombin consumption test of thrombocytopenic serum can be prolonged by adsorption on BaCO3 or reduced again by the addition of the sodium citrate eluate. The antihemophilic activity of thrombocytopenic blood disappears when the blood clots as in normal blood and autoprothrombin I is present in much smaller amounts than in normal serum. The authors suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1963
1963
1971
1971

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…or less) is not due to residual prothrombin in the serum but is due to the presence of a prothrombin-like derivative. 17 The same is true for the recalcified thrombocytopenic serum from normal plasma. The two-stage prothrombin determination of Ware and Seegers26 reveals less than 40 units per ml.…”
Section: Methodsmentioning
confidence: 84%
“…or less) is not due to residual prothrombin in the serum but is due to the presence of a prothrombin-like derivative. 17 The same is true for the recalcified thrombocytopenic serum from normal plasma. The two-stage prothrombin determination of Ware and Seegers26 reveals less than 40 units per ml.…”
Section: Methodsmentioning
confidence: 84%
“…I n this study, prothrombin was measured by a modified one-stage prothrombin time. In 1957, J o h n s o n and her associates (6) confirmed the finding that the serum prothrombin time of blood from patients with t h r o m b~c~t o p e n i a was short, (7) but observed that when the ~r o t h r o m b i n in the serum was measured by the two-stage method, it was as low as in the serum from normal blood. The implication arising from these findings that one-stage ~r o t h r o m b i n consumption test may not be a reliable determination of prothrombin prompted a restudy of prothrombin utilization comparing the one-stage with the two-stage method.…”
mentioning
confidence: 91%